2015
DOI: 10.1097/hjh.0000000000000504
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional role of the prorenin receptor in the human adrenocortical zona glomerulosa and in primary aldosteronism

Abstract: The presence of detectable plasma prorenin in primary aldosteronism patients, and the high expression of PRR in the normal human adrenal cortex, APA tissue, CD56+ aldosterone-producing cells, along with activation of CYP11B2 synthesis and ERK1/2 phosphorylation, suggest that the circulating and locally produced prorenin may contribute to the development or maintenance of human primary aldosteronism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Our data show cytoplasmic granular staining of PRR in RCCs, which could be associated with these intracellular phenomena. PRR has also been described in benign tumours, such as adrenal [46,47] and colorectal adenomas [27]. In agreement with this, our results showed that PRR was expressed in RO and with the same intensity as in ChRCC, tumours that are histogenetically related [6].…”
Section: Discussionsupporting
confidence: 91%
“…Our data show cytoplasmic granular staining of PRR in RCCs, which could be associated with these intracellular phenomena. PRR has also been described in benign tumours, such as adrenal [46,47] and colorectal adenomas [27]. In agreement with this, our results showed that PRR was expressed in RO and with the same intensity as in ChRCC, tumours that are histogenetically related [6].…”
Section: Discussionsupporting
confidence: 91%
“…Recarti et al [46] have detected high expression of (P) RR in APA tissues and HAC15 adrenocortical carcinoma cells that can produce aldosterone once treated with Ang II. Binding of prorenin and (P) RR could trigger the expression of the aldosterone synthase CYP11B2 and ERK1/2 phosphorylation, thus promoting the production and secretion of aldosterone [46].…”
Section: Aldosterone-producing Adenoma (Apa)mentioning
confidence: 99%
“…Recarti et al [46] have detected high expression of (P) RR in APA tissues and HAC15 adrenocortical carcinoma cells that can produce aldosterone once treated with Ang II. Binding of prorenin and (P) RR could trigger the expression of the aldosterone synthase CYP11B2 and ERK1/2 phosphorylation, thus promoting the production and secretion of aldosterone [46]. Furthermore, Yamamoto et al [15] revealed that both the mRNA and protein expression levels of (P) RR are elevated in tumor tissues of APAs relative to these levels in the matched non-neoplastic adrenal tissues and tissues from (See figure on previous page.)…”
Section: Aldosterone-producing Adenoma (Apa)mentioning
confidence: 99%
“…These findings may therefore indicate that (P)RR plays a crucial role in the CYP11B2 transcription through activation of the Wnt/ β -catenin signaling pathway. On the other hand, a previous in vitro study using HAC15 adrenocortical cells demonstrated that the binding of prorenin to (P)RR triggers the generation of angiotensin I from angiotensinogen, ensuring the formation of angiotensin II and activation of the AT1R leading to transcription of CYP11B2 and amplification of aldosterone production [ 24 ]. These findings and our immunohistochemical staining results raised the possibility that (P)RR plays an important role in the regulation and/or production of aldosterone through activation of CYP11B2 transcription in human APA tissues.…”
Section: Discussionmentioning
confidence: 99%